Customers Mal Wa Tamwil in The Event of Dissolution of The Body Law - Annisa Sayyid (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2023)
This study aims to identify and analyze the application of legal protection for depositors when a legal entity is disbanded with obstacles that hinder the fulfillment of the rights and obligations of the parties. The analysis utilizes a statutory and conceptual approach. The legal basis for protection for BMT customers is Law no. 1 of 2013 concerning Microfinance Institutions (LKM), specifically articles 24 and 25, which regulates the prevention of disputes or revocation of permits. Article 26 states that the Financial Services Authority (OJK) provides depository complaint services if it causes them to suffer losses. However, if the BMT is a cooperative legal entity, then it uses the basis of Law No. 25 of 1992, specifically article 54 concerning settlement. This difference in rules is one of the factors in the slow resolution of the problems of liquidated BMT customers. The government should provide clear rules regarding the institutional status of BMTs, so that the settlement of the legal protection of its customers becomes clear However, if the BMT is a cooperative legal entity, then it uses the basis of Law No. 25 of 1992, specifically article 54 concerning settlement. This difference in rules is one of the factors in the slow resolution of the problems of liquidated BMT customers. The government should provide clear rules regarding the institutional status of BMTs, so that the settlement of the legal protection of its customers becomes clear However, if the BMT is a cooperative legal entity, then it uses the basis of Law No. 25 of 1992, specifically article 54 concerning settlement. This difference in rules is one of the factors in the slow resolution of the problems of liquidated BMT customers. The government should provide clear rules regarding the institutional status of BMTs, so that the settlement of the legal protection of its customers becomes clear.